Prospek Agribisnis Berbasis Tanaman Hias Usaha Bungan Sedap Malam dan Anggrek Vanda Douglas (Tinjauan Khusus Usahatani, Harga dan Permintaan) - Agus Santosa (Caraka Tani: Journal of Sustainable Agriculture, 2006)
Along with development era and change of generation caused the revolution of cultivation and culture of Indonesian people, in term of good and service consumption. Demand of esthetic needs take a lot portion. This condition give opportunity for market player Ornamental Plant in many kinds of product to fulfill esthetic need for consumer. This paper object: 1) to show the business prospect on the several activity of Ornamental Plant business, and 2) to show the trend of Ornamental Plant demand. The method used Literature Study from many result of the research about Ornamental Plant by Agriculture Faculty at UPN “Veteran” Yogyakarta.Result of the research indicate that: 1) “Sedap Malam” flower farm by 230 farmers in Grabag Sub-District at Magelang District is profitable as much Rp. 23,718,753,- per hectare per year or Rp. 6,773,585,- per month, 2) Business of orchid cutting flower (Vanda Douglas) at UD. Vanditia in Mlati Sub-District, Sleman Regency of Yogyakarta for the first three years is profitable as much Rp. 345,916,725,- per hectare or Rp. 115,303,575,- per year per hectare with profit rate 56% per year per hectare, 3) Demand of Vanda Douglas orchid cutting flower in Borobudur Park at Magelang Regency and Vanditia Farm fluctuated that influence by religious event, price of another orchid, and price of Vanda Douglas orchid.In conclusion, Agribusiness on Ornamental Plant is proved have profitable and prospect to develop in the next period (era)